2021
DOI: 10.1038/s41372-021-01007-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing light and noise levels before and after a NICU change of design

Abstract: Objective. To compare light and sound levels before and after a change of design and evaluate these levels considering recommended NICU standards. Studydesign. A pre-test/post-test design. Light and sound levels were compared between the former open ward (OW) NICU of 34 beds and the current 40 bed unit composed of both pods and single-family rooms (SFR).Result. Light levels were significantly higher in the pod/SFR unit for all levels of care, days of the week and time of the day. These findings could be attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
3
1
0
1
Order By: Relevance
“…This is in line with previous studies that characterized light levels in different hospital settings, in which median daytime light levels ranged between 40-150 lux (Durrington et al, 2017;Fan et al, 2017;Greenfield et al, 2020;Lusczek and Knauert, 2021). In addition, in a study comparing two different NICU designs, it was found that daytime light levels were lower in an open ward design (comparable to the NICU in our study) compared to in pods and single-family rooms (69 vs. 368 lux) (Aita et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies that characterized light levels in different hospital settings, in which median daytime light levels ranged between 40-150 lux (Durrington et al, 2017;Fan et al, 2017;Greenfield et al, 2020;Lusczek and Knauert, 2021). In addition, in a study comparing two different NICU designs, it was found that daytime light levels were lower in an open ward design (comparable to the NICU in our study) compared to in pods and single-family rooms (69 vs. 368 lux) (Aita et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed elevated levels of noise in the investigated Brazilian NICU, consistent with findings from other published literature [19,[25][26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…When compared to other NICUs, our open bay NICU with an average SPL of 53 dB(A) does not seem to be a loud one; the staff is trained to lower their voices, we offer music therapy, and we encourage parents to communicate with their newborns. Correspondingly, in a recent study in Montreal even after change of the whole NICU architecture, an average sound pressure level of 49 dB(A) (coming from 58 dB(A)) has been reported [76]. Similar ranges have been reported in South India [77].…”
Section: Conclusion For the Newborn Inside The Incubatorsupporting
confidence: 60%